2007
DOI: 10.2169/internalmedicine.46.6457
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Reversible Splenial Lesion in Adult Meningitis: A Case Report and Review of the Literature

Abstract: We report the rare case of a 38-year-old man who suffered from aseptic meningitis. Brain magnetic resonance imaging showed an ovoid lesion with a high signal intensity on T2-and diffusion-weighted images in the splenium of the corpus callosum that completely disappeared within a week. There were no symptoms or signs associated with the lesion, and the prognosis was good. Although rare in adult patients, awareness of a reversible splenial lesion in meningoencephalitis is important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…Isolated and reversible lesion of the SCC has been reported in cases of encephalopathy (MERS) [4,5], antiepileptic drugs (AED), and/or alcohol toxicity [5], metabolic disorders [4,5] such as hypoglycemia, and reversible posterior leukoencephalopathy syndrome [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolated and reversible lesion of the SCC has been reported in cases of encephalopathy (MERS) [4,5], antiepileptic drugs (AED), and/or alcohol toxicity [5], metabolic disorders [4,5] such as hypoglycemia, and reversible posterior leukoencephalopathy syndrome [5].…”
Section: Discussionmentioning
confidence: 99%
“…Isolated and reversible lesions of the splenium of the corpus callosum (SCC) are usually revealed by brain magnetic resonance imaging (MRI) following mild encephalitis, alcohol toxicity, or even hypoglycemia. However, these radiological lesions were described in some patients with meningitis [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…[29,31] When hyponatremia occurs, the osmotic pressure of the cells in the corpus callosum is decreased and the increased free water entered into the cells leading to cytotoxic edema eventually. [15] Tani et al [96] reviewed clinical date of 24 patients with RESLES and found that all of them had fever, suggesting that fever may be associated with RESLES. The mechanism of fever to result in RESLES may be that fever increased the consumption of brain glucose, thereby reducing local effective osmolarity of brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Several viruses (influenza virus, adenovirus, mumps virus, varicella zoster virus [ 2 , 3 ], rotavirus [ 4 ], measles virus [ 5 ], and hepatitis A virus [ 6 ]) and bacteria ( Escherichia coli [ 7 ], Legionella pneumophila [ 8 ], and Mycoplasma pneumoniae [ 9 ]) have been reported to cause MERS, but bacteria are rarely the cause [ 2 , 3 ]. Staphylococcus aureus , especially, is a very rare cause of MERS, and only one such case has been reported so far [ 10 ].…”
Section: Introductionmentioning
confidence: 99%